Transition towards green banking: Role of financial regulators and financial institutions - Hyoungkun Park; Jong-Dae Kim (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
This paper provides an overview of green banking as an emerging area of creating competitive advantages and new business opportunities for private sector banks and expanding the mandate of central banks and supervisors to protect the financial system and manage risks of individual financial institutions. Climate change is expected to accelerate and is no longer considered only as an environmental threat because it affects all economic sectors. Furthermore, climate-related risks are causing physical and transitional risks for the financial sector. To mitigate the negative impacts, central banks, supervisors and policymakers started undertaking various green banking initiatives, although the approach taken so far is slightly different between developed and developing countries. In parallel, both private and public financial institutions, individually and collectively, are trying to address the issues on the horizon especially from a risk management perspective. Particularly, private sector banks have developed climate strategies and rolled out diverse green financial instruments to seize the business opportunities. This paper uses the theory of change conceptual framework at the sectoral, institutional and combined level as a tool to identify barriers in green banking and analyze activities that are needed to mitigate those barriers and to reach desired results and impacts.
Keywords: 650; Green banking; Sustainable banking; Climate change; Financial institutions; Central bank; Supervisor; Regulator; Financial sector; Theory of change; Climate risk